Pengaruh Literasi Keuangan Digital Terhadap Penggunaan Bijak Buy Now Pay Later: The Influence of Digital Financial Literacy on the Prudent Use of Buy Now Pay Later - Mutafaqih, Sandi; Hermawan, Yoni; Sartika, Sri Hardianti (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to analyze the influence of digital financial literacy on the prudent use of Buy Now Pay Later (BNPL) services among the 2022–2024 cohorts of Economic Education students at Siliwangi University. This research is motivated by the rapid growth of BNPL usage among the younger generation, which is frequently unaccompanied by a sufficient understanding of financial risks, thereby potentially leading to consumptive behavior and bad debt. This study employed a quantitative survey method involving 205 students selected via purposive sampling, with data collected through questionnaires. The results of the simple linear regression analysis yielded the equation y^​=11.505+0.791X, indicating that higher digital financial literacy corresponds to more prudent use of BNPL services. These findings confirm a positive and significant influence of digital financial literacy on the prudent use of BNPL and underscore the importance of enhancing digital financial literacy to foster healthier financial behaviors among students.